Online Shopping Attitude Among Youth in India - Kumar, R; Singh, V (International Journal of Computer Sciences and Engineering, 2025)
The purpose of this study is to explore the attitude of youth towards online shopping. Online shopping has a tremendous growth in India. It is a recent phenomenon in the field of E-business. It has become a new trend of shopping and is quickly becoming a vital part of lifestyle. It offers the customer a wide range of products and services wherein he is able to compare the price quoted by diverse suppliers and also choose the best deal from it. Through online shopping, consumers can buy the selected product rapidly by doing some clicks from home or work saving time and energy in spite of the larger distance arising from the endless and unlimited market offered by the internet. Online shopping has seen a huge growth in recent years. The study found that most of the young people doing online shopping. Further, the study found that in case of gender, female respondents with higher average online shopping expenditure than that of the male respondents